The genus Nactus (Lacertilia: Gekkonidae): a phylogenetic analysis and description of two new species from the Papuan Region - Kraus, Fred (Zootaxa, 2005)
Two new geckos from islands off the southeastern tip of New Guinea are not readily assignable to any currently defined genus but appear closely related to Nactus. The defining features of Nactus, however, have been uncertain because of variation among species assigned to this group, character convergence with other genera, and varying character emphases of different researchers. Moreover, relationships of Nactus to other gekkonine genera are uncertain because of homoplasy among the few characters used to infer higher-level relationships within Gekkoninae. I performed an analysis of phylogenetic relationships of my two new species to members of Nactus using a variety of other gekkonine and diplodactyline genera as outgroups. The results indicate the two new species are derived members of the genus Nactus that have undergone evolutionary reversal of some of the characters previously used to distinguish this genus. A further result of my analyses is that Nactus as currently conceived may prove paraphyletic or polyphyletic because its two most morphologically divergent species fail to cluster with the remaining members of this genus in all analyses. The two new species are herein described as Nactus sphaerodactylodes sp. nov. and Nactus acutus sp. nov. and may readily be distinguished from the other members of the genus by a variety of scalational features.